THE DOCUMENTARY HERITAGE OF JOZEF KOWALEWSKI AT THE VILNIUS UNIVESITY LIBRARY: AN ATTEMPT OF RECONSTRUCTION - KARŽELIENĖ, LILIJA; ŠULGIENĖ, NIJOLĖ (Knygotyra, 2012)
In 2010, Vilnius University (further VU) marked the 200th anniversary of academic studies in orientalistics, and in 2011 the 210th birth anniversary of VU alumnus, progenitor of mongolistics in Russia Jozef Kowalewski (Józef Szczepan Kowalewski, Осип Михайлович Ковалевский – 1801–1878) was celebrated with a special exhibition dedicated to him and held at VU Library. These events aroused interest in the fate of J. Kowalewski‘s personal library donated to the University by his wife Anna Kowalewska in 1883. The reconstruction of J. Kowalewski’s documentary heritage was a venture to find out in what VU Library departments and how many items of his personal collection are being kept today. Pursuant to the archival documents and the publications of the personal library, it became clear that J. Kowalewski’s documentary heritage at VU Library was concentrated in the departments of Book Storage, Manuscript, and Rare Book. In the course of research, the information published in the mass media about the number of books in J. Kowalewski’s personal library was expanded and corrected: instead of the known 444 titles, 1250 publications formerly owned by J. Kowalewski were identified. The ownership marks found in the books showed that J. Kowalewski had been collecting his library from the beginning of his studies in Vilnius in 1817 until his death in Warsaw in 1878. J. Kowalewski’s personal books are being entered into the electronic catalogue, while the already digitized manuscripts will become a source for studies and investigation.
Keywords: ...